HUBUNGAN ANTARA TINGKAT DAN INTENSITAS SERANGAN HAMA PENGGEREK BUAH KAKAO (conopomorpha cramerella) TERHADAP PRODUKSI KAKAO DI KECAMATAN MANYAK PAYED - Sara, Fatia; Mulyani, Cut; Iswahyudi, Iswahyudi (University of Prof. Dr. Hazairin, SH, 2023)
The purpose of this study was to determine the effect of cocoa pod borer (CPB) pest attack intensity on cocoa production in Manyak Payed District. This study used a survey method, sampling was carried out using a